Evaluation of Acute and Repeated Dose Oral Toxicity of Phoenix dactylifera L. Pollen Methanolic Extract in Rats - Abdelrahim, Musab A. M.; Ahmed, Elhadi M. M. (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Pollen of the date palm (Phoenix dactylifera L.) has been used for thousands of years as a traditional herbal medicine for improving fertility. However, safety of plant-derived materials is an important concern to human health, and herbal remedies should be taken with adequate knowledge about their toxicity, adverse effects, purity, appropriate dosage and dose limits. The current work was undertaken to evaluate the safety of date palm pollen (DPP) and to classify it according to its oral toxicity in rats. The experiments were done according to the reported guidelines of the Organization for Economic Co-operation and Development (OECD) to assess the acute and repeated dose oral toxicity in rats. The obtained results showed neither death nor sign of toxicity or abnormality in any of the animals throughout the experimental period regarding acute and repeated dose oral toxicity. Also the results of the hematological and clinical biochemistry determinations showed no significant differences between the control and DPP-treated rat groups. It could be concluded that, the tested plant material is a relatively safe substance and its approximate LD50 defined by 2000mg/kg < LD50 < 5000mg/kg according to the OECD tests guidelines.